Assessment of Groundwater Quality Along the Coastal Aquifers of Kollam Corporation, Southern Kerala, India - Zulthana Nima; N. SHINU; Anoop S.; Yamuna Sali A.S.; Anjana A.V. Panicker (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Groundwater serves as a primary resource for drinking water, irrigation, and industrial activities, primarily accessed through wells.  Out of the 3% of the global freshwater supply, a significant portion is locked in glaciers, and the remainder is present as groundwater.  In India, limited resources and rising pollution rates make groundwater a critical resource, providing nearly 80% of the country’s drinking water. Aim: The present study examines the quality of groundwater in the Corporation area of Kollam, a prominent coastal district in southern Kerala, India, focusing on its potability and suitability for irrigation. Methods: Twelve pre-monsoon water samples were collected from wells across the area and analyzed for physical and chemical parameters to assess the influence of natural and anthropogenic factors on groundwater quality. Poor water quality can severely impact human health as well as agricultural productivity, particularly in regions where groundwater is the primary source of water. The analyzed data were compared with the drinking and irrigation water quality standards set by the Bureau of Indian Standards (BIS) and the World Health Organization (WHO). Results: The study shows that the groundwater system exhibits an acidic characteristic due to continuous interaction with the lateritic aquifer. The samples predominantly belong to the Na-Cl or Na-HCO3 types, indicating the influence of seawater intrusion.  Most samples met the criteria for ‘good-quality irrigation water, while others fell in the classification for ‘poor-quality. Conclusion: The findings highlight the increasing challenges associated with groundwater utilization and emphasize the importance of sustainable groundwater management practices in Kollam, a fast-growing coastal urban center of the state.